MANAJEMEN KOMUNIKASI PEMASARAN BAZNAS KOTA SAMARINDA DALAM PENYALURAN ZAKAT, INFAK, DAN SADAQAH - Sarwo Eddy, Camelia Verahastuti, dan Aidar Erika Toding Pali (Prodi Ilmu Administrasi Negara, 2020)
This study aims to analyze the marketing communication management of the City of Amil Zakat (BAZNAS) of Samarinda City in the implementation of zakat, infaq, and sadaqah (ZIS) to the community in the city of Samarinda and surrounding areas. The method used in this research is a qualitative descriptive method through data collection techniques, namely interviews, observation, and literature review. The results of this study indicate that Baznas organizational communication management includes planning, organizing, monitoring and evaluating. Marketing communication management is carried out to support a series of programs and social activities carried out by Baznas and stakeholders